Key attributes for effective knowledge brokering at the interface of environmental science and management - Denis B. Karcher; Christopher Cvitanovic; R. M. Colvin; Ingrid van Putten; Ramona Dalla Pozza; Stephen Posner (Sustainability Science, 2025)
Spanning the boundaries between research and decision-making is critical for supporting environmental management. One way to do so is through knowledge brokers who, among other things, work to build social networks among decision-makers and researchers, facilitating their interaction and exchange of knowledge. While knowledge brokering has received increasing attention in the literature, critical gaps in our knowledge limit their effective recruitment and implementation, which demands for a better understanding of the personal attributes needed for their success. Such an understanding is also necessary to support the evaluation of knowledge brokering activities. Therefore, in this study, we investigate the question ‘what are the most important attributes for being a knowledge broker at the interface of environmental research and management’, and how is knowledge brokering evaluated. We do so through the study of Australia’s National Environmental Science Program (NESP) which employs a range of professional knowledge brokers, 14 of whom participated in this study. Specifically, we performed a quantitative ranking exercise (Q-methodology) and an online survey. Results show that the most important attributes to knowledge brokering were interpersonal social competencies of a unifying nature. As such, Being good at seeing opportunities for collaboration, Being able to tailor communication to different audiences, and Being able to ask questions were the most highly ranked attributes. In the dimension of evaluation, survey results show that NESP knowledge brokers are mainly evaluated through metrics relating to immediate delivery and engagement (mostly quantitative measures) and medium-term impact on end-users (qualitative measures). However, participants envisioned better options to capture the impact/value of knowledge brokering by evaluating long-term impacts and efforts throughout the full brokering process to better capture value addition in line with their goals, strategies, and required attributes. The new knowledge generated through our findings offers an applied contribution to the practice of knowledge brokering, suggesting that knowledge brokering is a distinct and complex career whereby different knowledge brokers with complementary skill sets appear relevant to perform all tasks along a knowledge brokering timeline. As such, our results also emphasize the need for bespoke approaches to evaluation that are tailored towards the diverse goals, strategies, and personal contributions of knowledge brokers to support their career progression and maximise outcomes.

Integrating team science into interdisciplinary graduate education: an exploration of the SESYNC Graduate Pursuit - Kenneth E. Wallen; Karen Filbee-Dexter; Jeremy B. Pittman; Stephen M. Posner; Steven M. Alexander; Chelsie L. Romulo; Drew E. Bennett; Elizabeth C. Clark; Stella J.M. Cousins; Bradford A. Dubik; Margaret Garcia; Heather A. Haig; et al. (Journal of Environmental Studies and Sciences, 2019)